2019
DOI: 10.1016/j.ctro.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Learning from scanners: Bias reduction and feature correction in radiomics

Abstract: Highlights Typically encountered CT exposure variations result in radiomics values distortion. Proposed correction method suppresses the non-tumor related variation in radiomics. The clinical relevance was shown using a 221 lung cancer patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 13 publications
4
57
0
3
Order By: Relevance
“…Note: Modelling does not have a letter associated with since there is no consensus on the best statistical modelling strategies. Problem area Potential problems Potential solutions Image acquisition A Different scanners and acquisition protocols affect feature reproducibility [ [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] ] Image phantoms on different scanners to provide baseline [ 79 ], establish credibility of scanners and protocols [ 84 ], catalogue reproducible features [ 86 , 90 ], model a correction algorithm [ 89 ], harmonize data [ 91 ]. B Patient motion affects feature reproducibility [ 80 , 92 , 93 ] Set motion tolerances, reduce ROI boundaries [ 80 ], use single phase from 4D images [ 92 ], find robust features using 4DCT data [ 93 ].…”
Section: Reported Methodological Limitations Of Ct Based Radiomics Stmentioning
confidence: 99%
See 2 more Smart Citations
“…Note: Modelling does not have a letter associated with since there is no consensus on the best statistical modelling strategies. Problem area Potential problems Potential solutions Image acquisition A Different scanners and acquisition protocols affect feature reproducibility [ [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] ] Image phantoms on different scanners to provide baseline [ 79 ], establish credibility of scanners and protocols [ 84 ], catalogue reproducible features [ 86 , 90 ], model a correction algorithm [ 89 ], harmonize data [ 91 ]. B Patient motion affects feature reproducibility [ 80 , 92 , 93 ] Set motion tolerances, reduce ROI boundaries [ 80 ], use single phase from 4D images [ 92 ], find robust features using 4DCT data [ 93 ].…”
Section: Reported Methodological Limitations Of Ct Based Radiomics Stmentioning
confidence: 99%
“…Indeed, one study showed that using a controlled protocol across different CT scanners reduced feature variability by over 50 % compared to using local protocols [79]. Other studies used post-extraction deep learning [100] or correction factors [89] to reduce feature variability.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…One proposed solution is to eliminate the dependency of features on a certain factor by modeling the relationship and applying corrections accordingly. This had been explored recently for different CT exposure settings [123]. Another method to eliminate the dependency is to convert images using deep learning, in order to simulate reconstruction with different settings, which was shown to improve CT radiomics' reproducibility for images reconstructed with different kernels [62].…”
Section: Reduce Radiomics' Dependencymentioning
confidence: 99%
“…The correct and robust application of radiomics analysis has to be investigated, since the algorithm-based analysis of quantitative date is not standardized within different institutions, or even within single institutions, and can easily be performed differently. Independently of software-and hardware-induced variability [116][117][118][119][120][121], texture analysis is also hindered by uncertainties in patient immobilization and organ movements, especially with regard to MRI examinations [122,123]. On top of this, its usage for treatment decisions and treatment planning has to be investigated in prospective trials including ex-vivo, in-vivo volunteer and in-vivo patient examinations allowing for founded conclusions about its usage.…”
Section: Current Limitations Of Radiomicsmentioning
confidence: 99%